Treatment method of agricultural by-products and application of agricultural by-products in preparation of lignin and cellulose nanofibers

By pretreating agricultural by-products using co-solvents of γ-valerolactone and water, the problems of resource waste and environmental pollution in the prior art are solved, and efficient extraction and separation of cellulose and lignin are achieved, and cellulose nanofibers with excellent performance and high thermal stability lignin are prepared.

CN119775589APending Publication Date: 2025-04-08INST OF AGRO FOOD SCI & TECH CHINESE ACADEMY OF AGRI SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411675279.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the preparation of cellulose nanofibers and lignin, the prior art mainly relies on reagents such as acids and eutectic solvents, which leads to waste of resources, environmental pollution and recycling difficulties, and fails to achieve comprehensive and high-value utilization of agricultural by-products.

Method used

The agricultural by-products were pretreated by co-solvent of γ-valerolactone (GVL) and water. Through the breakage of strong hydrogen bonds and the depolymerization of lignin, cellulose, lignin and hemicellulose were effectively separated, and cellulose nanofibers were prepared by high-pressure homogenization.

Benefits of technology

Efficient extraction and separation of cellulose and lignin are achieved, and cellulose nanofibers with excellent performance and high thermal stability lignin are prepared. The method is green, non-toxic, environmentally friendly, and suitable for sustainable use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775589A_ABST
    Figure CN119775589A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-value utilization of agricultural by-products, in particular to a treatment method of the agricultural by-products and application of the agricultural by-products to preparation of lignin and cellulose nanofibers. The treatment method of the agricultural by-products comprises the following steps: S1, drying the agricultural by-products and then crushing the agricultural by-products to obtain agricultural by-product powder; s2, mixing the agricultural by-product powder with a cosolvent, and carrying out a reaction to obtain a mixed slurry after the reaction; carrying out vacuum filtration on the mixed slurry to respectively obtain solid and liquid fractions rich in cellulose; wherein the agricultural by-product contains lignocellulose, and the cosolvent comprises a mixture of water and gamma-valerolactone. According to the method, the agricultural by-products rich in cellulose are pretreated through the cosolvent composed of gamma-valerolactone and water, the lignocellulose structure can be effectively destroyed, meanwhile, solids rich in cellulose and lignin are obtained, and high-value utilization of the agricultural by-products is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-value utilization of agricultural by-products, and in particular to a method for processing agricultural by-products and application of the method in preparing lignin and cellulose nanofibers. Background Art

[0002] Against the backdrop of the rapid and increasing depletion of fossil energy, the research focus of modern industry has gradually shifted to the use of sustainable resources. Lignocellulosic biomass is a widely available, renewable and environmentally friendly resource. Agricultural byproducts are high-quality raw materials for biorefining and material production. For example, sweet potato vines, potato residues, pomace, corn stalks, corn cobs, rice husks and other biomass materials rich in lignocellulose can be developed and utilized as raw materials for the preparation of cellulose and lignin. Cellulose nanofibers (CNFs) are a bio-based material with excellent properties, such as high strength, high rigidity, good biocompatibility and good dispersibility. Their diameter is usually less than 100 nm and their aspect ratio is usually greater than 50. CNFs have broad application potential in many fields, such as food, food packaging, drug delivery, wound dressings, filtration materials, etc. Lignin is a natural organic polymer compound with the advantages of UV resistance and antioxidant properties. Lignin is often used as a reinforcing agent for composite materials, agriculture and soil improvement, etc.

[0003] Lignocellulosic biomass has a complex and stubborn structure, and pretreatment is required to destroy its structure before cellulose and lignin can be further extracted. To date, there are many pretreatment methods for lignocellulosic biomass, including chemical methods, physical methods, and biological methods. Chemical methods often use strong acids (such as sulfuric acid, hydrochloric acid) and strong bases (sodium hydroxide, calcium hydroxide) to break the chemical bonds of lignocellulose, but there are disadvantages such as corrosion of equipment and pollution of the environment; physical methods usually use mechanical, thermal and physical crushing to break the structure of lignocellulose, but there are disadvantages such as high energy consumption, high cost, and harsh operating conditions; biological methods usually use fungi and other microorganisms to decompose lignocellulose, but there are disadvantages such as long processing time and low efficiency. In order to solve the problems existing in the above traditional pretreatment methods, it is urgent to invent a green pretreatment method that can effectively separate cellulose and lignin and can sustainably prepare cellulose nanofibers with excellent performance.

[0004] In recent years, domestic and foreign scholars and enterprise technicians have carried out a lot of work around the high-value utilization of lignocellulosic biomass. CN116536948B discloses a method for preparing nanocellulose by acid hydrolysis of grass raw materials. The invention uses a choline chloride / 5-hydroxyisophthalic acid deep eutectic solvent system to pretreat the raw materials, dissolve hemicellulose and lignin, and use sulfuric acid to hydrolyze after bleaching to obtain nanocellulose. CN117230542B discloses a phosphorylated cellulose nanofiber and a method for preparing it. The invention mixes cellulose raw materials, phosphates, urea and deionized water, heats and crushes them, uses a single-screw extruder to extrude and dehydrate, and then sends them to a drying and curing device for heating, drying and high-temperature curing. After mixing with deionized water, they are mechanically ground and homogenized at high pressure to obtain phosphorylated cellulose nanofibers. CN118702935A discloses a method for preparing lignin gel, which prepares choline chloride and lactic acid low eutectic solvents, grinds and sieves biomass raw materials, mixes them with the low eutectic solvent in a certain mass ratio, places them in an oven for reaction, and obtains a filtrate rich in lignin after suction filtration. The filtrate rich in lignin, resorcinol, formaldehyde and the low eutectic solvent are mixed and stirred according to a proportion, and then placed in an oven for reaction to obtain lignin gel.

[0005] At present, the research on the preparation of cellulose nanofibers and lignin mainly uses reagents such as acids and low eutectic solvents, which are difficult to recycle and may cause environmental pollution. In addition, most studies are to extract cellulose from biomass by destroying and hydrolyzing lignin, which has caused a certain waste of resources and has not yet achieved a comprehensive high-value utilization of agricultural by-products. Summary of the invention

[0006] In order to solve the above problems in the prior art, the present invention provides a method for processing agricultural by-products and its application in preparing lignin and cellulose nanofibers, so as to simultaneously prepare lignin and cellulose nanofibers and realize high-value utilization of agricultural by-products.

[0007] Based on this, the present invention has the following technical solutions: In a first aspect, the present invention provides a method for processing agricultural by-products, characterized in that it comprises: S1: drying and crushing the agricultural by-product to obtain agricultural by-product powder; S2: mixing the agricultural byproduct powder with a co-solvent and reacting the mixture to obtain a mixed slurry; vacuum filtering the mixed slurry to obtain cellulose-rich solid and liquid fractions, respectively; The agricultural byproducts contain lignocellulose, and the co-solvent comprises a mixture of water and γ-valerolactone.

[0008] At present, the existing technology mainly uses reagents such as acids and low eutectic solvents to destroy and hydrolyze lignin to achieve the purpose of extracting cellulose from biomass, which not only leads to a waste of lignin resources, but also makes this method difficult to recycle and easily pollutes the environment. The present invention finds that by pretreating cellulose-rich agricultural byproducts with a co-solvent composed of γ-valerolactone (GVL) and water (H2O), the cellulose-rich solid and lignin can be obtained while the cellulose-rich solid is further prepared by high-pressure homogenization to prepare cellulose nanofibers (CNFs), thereby realizing the high-value utilization of agricultural byproducts.

[0009] Specifically, the present invention finds that the strong hydrogen bond formed between GVL and H2O is conducive to the breaking of the strong hydrogen bond in lignin, and the methyl groups of GVL interact with the methyl groups of lignin to promote the depolymerization of lignin and dissolve lignin in GVL; water can promote the depolymerization of hemicellulose, and cellulose is retained in the solid residue. The pretreatment process can effectively separate cellulose, lignin and hemicellulose. At the same time, the co-solvent formed by GVL and H2O is green, non-toxic and highly stable, and can effectively avoid pollution to the environment.

[0010] In the present invention, the agricultural by-products are rich in cellulose and may be one or more of sweet potato vines, potato residues, fruit residues, corn stalks, corn cobs and rice husks, etc., which are not limited here.

[0011] The processing method of the present invention is simple and easy to operate, has no harm to human health, is relatively green and pollution-free to the environment, and can realize the high-value recycling of agricultural by-products.

[0012] Preferably, in the co-solvent, the volume ratio of water to γ-valerolactone is (1-4): (1-4).

[0013] Preferably, S2 comprises: mixing and reacting the agricultural by-product powder, co-solvent and catalyst to obtain a mixed slurry after the reaction; vacuum filtering the mixed slurry to obtain cellulose-rich solid and liquid fractions, respectively; wherein the catalyst comprises a metal salt; preferably, the metal salt comprises one or more of NaCl, MgCl2, AlCl3 and FeCl3.

[0014] The present invention finds that the pretreatment efficiency can be effectively improved by introducing the above catalyst during pretreatment.

[0015] In the present invention, by using co-solvents and catalysts at preferred concentrations and pre-treating the raw materials at a specific temperature and time, the yield and colloidal stability of the obtained cellulose nanofibers can be improved.

[0016] Preferably, the concentration of the metal salt in the aqueous phase of the co-solvent is 5 wt % to 30 wt %.

[0017] Preferably, based on the volume of the mixture of the co-solvent and the catalyst, 0.05-0.2 g of the agricultural by-product powder is added per milliliter of the mixture.

[0018] Preferably, in S2, the reaction temperature is 70°C to 190°C; more preferably, the reaction temperature is 150°C to 190°C, which can further promote the depolymerization of hemicellulose.

[0019] Preferably, the reaction time is 1 h to 6 h.

[0020] Preferably, S2 further includes the following processing steps: S3: The liquid fraction is mixed with water, and then allowed to stand and subjected to a first centrifugation treatment in sequence, and the obtained precipitate is lignin; at the same time, the cellulose-rich solid is bleached and subjected to a second centrifugation treatment in sequence, and then the obtained lower precipitate is mixed with water to obtain a suspension, and the suspension is subjected to high-pressure homogenization and freeze-drying in sequence to obtain cellulose nanofibers.

[0021] In the present invention, the cellulose-rich solid cellulose is subjected to the above treatment to prepare cellulose nanofibers with excellent performance.

[0022] Preferably, the volume ratio of the liquid fraction to water is 1:(2-10); and the rotation speed of the first centrifugal treatment is 7000 r / min-10000 r / min.

[0023] More preferably, the first centrifugation treatment time is 10 min to 30 min.

[0024] In the present invention, by using the anti-solvent exchange method, water is added in a preferred ratio to precipitate lignin in water. Furthermore, by using the preferred centrifugal speed and time, the yield of the obtained lignin can be maximized.

[0025] Further preferably, the supernatant obtained from the first centrifugation treatment is subjected to vacuum distillation to recover water and γ-valerolactone respectively.

[0026] In the present invention, GVL can be recovered by vacuum distillation, which not only reduces the cost but also realizes the recycling of reagents.

[0027] In the present invention, the preferred high-pressure homogenization treatment conditions and the preferred suspension concentration are adopted, so that the yield and colloidal stability of the obtained cellulose nanofibers can be better, the average diameter of the cellulose nanofibers can be smaller, and the application range of the nanomaterials can be expanded.

[0028] Preferably, the bleaching temperature is 70° C. to 90° C., the bleaching time is 4 h to 6 h; the concentration of the suspension is 0.1wt% to 0.5wt%, the pressure of the high-pressure homogenization is 20 MPa to 80 MPa, and the number of cycles of high-pressure homogenization is 2 to 8 times.

[0029] In the present invention, conventional bleaching agents such as hydrogen peroxide can be used for bleaching, and the concentration of hydrogen peroxide is about 30 wt%.

[0030] In the present invention, the above-mentioned specific pretreatment conditions are optimized, and the subsequent method of preparing cellulose nanofibers by high-pressure homogenization can play a better role in continuous production and improve the yield of cellulose nanofibers and lignin.

[0031] In a second aspect, the present invention provides an application of the method for processing agricultural by-products in preparing lignin and / or cellulose nanofibers; preferably, the method for processing agricultural by-products is applied to simultaneously preparing lignin and cellulose nanofibers.

[0032] In a third aspect, the present invention provides lignin, which is produced by the above-mentioned method for processing agricultural by-products.

[0033] In the present invention, the lignin obtained by the above-mentioned agricultural byproduct treatment method has high thermal stability, and the maximum thermal degradation temperature can reach 334.45°C, which is significantly better than commercial lignin (maximum thermal degradation temperature reaches 310.86°C). The lignin is a GSH type structure, mainly composed of guaiacyl and p-hydroxyphenyl, and also contains a small amount of syringyl.

[0034] In a fourth aspect, the present invention provides a cellulose nanofiber produced by the above-mentioned method for processing agricultural by-products.

[0035] In the present invention, the cellulose nanofibers obtained by the above-mentioned agricultural by-product processing method have a filamentous structure, a diameter range of 11.20~38.45 nm, an average diameter of 23.33 nm, and a Zeta potential value of -27.23±0.59 mV. Preferably, the cellulose nanofibers retain the cellulose type I structure and have a crystallinity of 39.41%. The cellulose nanofibers preferably have higher thermal stability, with a maximum thermal degradation temperature of 329.03°C; which is significantly better than commercial CNFs (maximum thermal degradation temperature of 297.45°C).

[0036] The technical solution of the present invention has the following beneficial effects: (1) The treatment method adopted by the present invention can be widely applied to various existing agricultural and forestry by-products.

[0037] (2) The reagent used in the present invention is a green organic solvent, which does not damage instruments and equipment, is safe and non-toxic to the human body, is green and environmentally friendly, can be recycled and reused, reduces the cost of waste liquid treatment, improves the pretreatment efficiency, and significantly improves the product yield.

[0038] (3) The present invention can extract lignin while extracting cellulose, thereby realizing an efficient one-step separation of cellulose, lignin and hemicellulose. The prepared cellulose nanofibers have good dispersibility and stability, high crystallinity and good thermal stability. The prepared lignin has good thermal stability. Both have broad application prospects.

[0039] (4) The reaction conditions of the present invention are mild, the operation is simple, and it is easy to perform. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 It is a schematic diagram of the process flow of Example 1 provided by the present invention.

[0042] Figure 2 AFM images of CNFs obtained in Examples 1-3 provided by the present invention.

[0043] Figure 3 AFM images of CNFs obtained in Examples 4-5 provided by the present invention.

[0044] Figure 4 AFM images of CNFs obtained in Comparative Examples 1-2 provided by the present invention.

[0045] Figure 5 Fourier transform infrared spectra of the raw materials provided by the present invention, CNFs prepared in Example 1, commercial CNFs, lignin prepared in Example 1, and commercial lignin.

[0046] Figure 6 Weight loss graph (A) of the raw material provided by the present invention, CNFs prepared in Example 1, commercial CNFs, lignin prepared in Example 1, and commercial lignin, derivative weight loss graph (B) and maximum thermal degradation temperature graph (C). DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.

[0049] In the following examples of the present invention, cellulose nanofibers and lignin were prepared using sweet potato vines as raw materials.

[0050] Example 1 This embodiment provides a method for continuously preparing cellulose nanofibers and lignin, which is carried out according to the following steps: (1) Cleaning, drying and crushing the sweet potato vines; (2) 10 g of the vine powder crushed in step (1) was placed in a reactor and mixed with 150 mL of GVL / H2O co-solvent (GVL / H2O = 1 / 4, v / v), and 18 g of NaCl was added as a catalyst, and the mixture was reacted at 170 °C in the reactor for 4 h; (3) vacuum filtering the pretreated residue in step (2) to obtain solid and liquid fractions rich in cellulose; the liquid fraction was mixed with 1500 mL of water, allowed to stand for 12 h, and centrifuged at 10000 r / min for 30 min to obtain a precipitate, and the precipitate was freeze-dried to obtain a lignin sample; (4) mixing the cellulose-rich solid from step (3) with 50 mL of 30 wt % hydrogen peroxide, bleaching in a water bath at 85° C. for 4 h, and centrifuging at 10,000 r / min for 30 min to obtain a bleached cellulose precipitate; (5) The bleached cellulose precipitate obtained by centrifugation in step (4) is freeze-dried to prepare a 0.2 wt% suspension, and the homogenization is repeated 4 times at 40 MPa using a high-pressure homogenizer. The resulting suspension is freeze-dried to obtain CNFs.

[0051] Example 2 This embodiment provides a method for continuously preparing cellulose nanofibers and lignin, which is carried out according to the following steps: (1) Cleaning, drying and crushing the sweet potato vines; (2) 10 g of the vine powder crushed in step (1) was placed in a reactor and mixed with 150 mL of GVL / H2O co-solvent (GVL / H2O = 2 / 3, v / v), and reacted in the reactor at 170 °C for 4 h; (3) vacuum filtering the pretreated residue in step (2) to obtain solid and liquid fractions rich in cellulose; the liquid fraction was mixed with 1200 mL of water, allowed to stand for 12 h, and centrifuged at 10000 r / min for 30 min to obtain a precipitate, and the precipitate was freeze-dried to obtain a lignin sample; (4) mixing the cellulose-rich solid from step (3) with 50 mL of 30 wt % hydrogen peroxide, bleaching in a water bath at 85° C. for 4 h, and centrifuging at 10,000 r / min for 30 min to obtain a bleached cellulose precipitate; (5) The bleached cellulose precipitate obtained by centrifugation in step (4) is freeze-dried to prepare a 0.2 wt% suspension, and the homogenization is repeated 4 times at 60 MPa using a high-pressure homogenizer. The resulting suspension is freeze-dried to obtain CNFs.

[0052] Example 3 This embodiment provides a method for continuously preparing cellulose nanofibers and lignin, which is carried out according to the following steps: (1) Cleaning, drying and crushing the sweet potato vines; (2) Place 10 g of the vine powder crushed in step (1) in a reactor and mix with 150 mL of GVL / H2O co-solvent (GVL / H2O = 2 / 3, v / v), and react at 150 °C in the reactor for 2 h; (3) vacuum filtering the pretreated residue in step (2) to obtain solid and liquid fractions rich in cellulose; the liquid fraction was mixed with 900 mL of water, allowed to stand for 12 h, and centrifuged at 10,000 r / min for 30 min to obtain a precipitate, and the precipitate was freeze-dried to obtain a lignin sample; (4) mixing the cellulose-rich solid from step (3) with 50 mL of 30 wt % hydrogen peroxide, bleaching in a water bath at 85° C. for 4 h, and centrifuging at 10,000 r / min for 30 min to obtain a bleached cellulose precipitate; (5) The bleached cellulose precipitate obtained by centrifugation in step (4) is freeze-dried to prepare a 0.2 wt% suspension, and the homogenization is repeated 8 times at 40 MPa using a high-pressure homogenizer. The resulting suspension is freeze-dried to obtain CNFs.

[0053] Example 4 The present embodiment provides a continuous preparation method of cellulose nanofibers and lignin, which is different from the embodiment 1 in that: in step (2), 10 g of the crushed vine powder is placed in a reactor and mixed with 150 mL of GVL / H2O co-solvent (GVL / H2O = 1 / 4, v / v), and 18 g of NaCl is added as a catalyst, and the mixture is reacted in the reactor at 90°C for 2 h; in step (3), the liquid fraction is mixed with 1500 mL of water, allowed to stand for 12 h, and centrifuged at 5000 r / min for 15 min to obtain lignin; in step (5), homogenization is repeated 4 times at 20 MPa using a high-pressure homogenizer, and the obtained suspension is freeze-dried to obtain CNFs.

[0054] Example 5 This embodiment provides a method for continuously preparing cellulose nanofibers and lignin. Compared with Embodiment 1, the difference is that no catalyst NaCl is added during the reaction.

[0055] Comparative Example 1 This comparative example provides a continuous preparation method of cellulose nanofibers and lignin, which is different from Example 1 in that: in step (2), 10 g of the crushed vine powder is placed in a reactor and mixed with 150 mL of GVL, and reacted in the reactor at 170°C for 4 h; in step (3), the liquid fraction is mixed with 1500 mL of water, allowed to stand for 2 h, and centrifuged at a speed of 10000 r / min for 30 min to obtain lignin; in step (5), a high-pressure homogenizer is used to repeat homogenization twice at 40 MPa, and the obtained suspension is freeze-dried to obtain CNFs.

[0056] Comparative Example 2 This comparative example provides a continuous preparation method of cellulose nanofibers and lignin, which is different from Example 1 in that: in step (2), 10 g of the crushed vine powder is placed in a reactor and mixed with 150 mL of H2O, and reacted in the reactor at 170°C for 4 h; in step (3), the liquid fraction is mixed with 300 mL of water, allowed to stand for 12 h, and centrifuged at a speed of 10,000 r / min for 30 min to obtain lignin; Experimental Example 1: Analysis of the yield of cellulose nanofibers and lignin The yields of CNFs and lignin were determined by gravimetric analysis. All experiments were repeated three times independently and the results are expressed as mean ± standard deviation. The weight of the final freeze-dried sample was designated as M2 and the dry weight of the vine powder after initial crushing was determined as M1. The yield was calculated as follows: The test results are as follows: As shown in Table 1, the yields of CNFs and lignin in Examples 1-3 are significantly higher than those in Example 4 and Comparative Examples 1-2, wherein the yields of CNFs and lignin obtained in Example 1 are the highest, and the yields of CNFs and lignin obtained in Comparative Example 2 are the lowest. This indicates that the use of GVL / H2O / NaCl co-solvent pretreatment and the preferred conditions in the present invention significantly improves the yields of CNFs and lignin.

[0057] Table 1 Results of yields of CNFs and lignin

[0058] Note: Different letters (af) in the same column indicate significant differences among the values ​​( p <0.05).

[0059] Experimental Example 2: Zeta potential analysis of cellulose nanofibers The CNFs suspension was diluted to 2 mg / mL and dispersed under ultrasonic treatment for 5 min. Deionized water was used as the dispersant to measure the Zeta potential. The Malvern Nano Particle Size Analyzer experimental conditions were set as follows: temperature 25°C, scattering angle 173, and equilibrium time 3 min. Three readings were taken.

[0060] The test results are as follows: As shown in Table 2, the Zeta potential trend of CNFs is similar to that in Table 1. The absolute values ​​of the Zeta potential of CNFs in Examples 1-3 are significantly higher than those in Examples 4 and Comparative Examples 1-2, among which the absolute value of the Zeta potential of CNFs obtained in Example 1 is the highest, and the absolute value of the Zeta potential of CNFs obtained in Comparative Example 2 is the lowest. This indicates that the preferred conditions of the present invention significantly improve the colloidal stability of CNFs.

[0061] Table 2 Zeta potential results of CNFs

[0062] Note: Different letters (af) in the same column indicate significant differences among the values ​​( p <0.05).

[0063] Experimental Example 3: Atomic Force Microscopy (AFM) Analysis of Cellulose Nanofibers The CNFs suspension was diluted to 0.05 mg / mL, and 10 µL of the CNFs suspension was dropped onto a 1×1 cm square mica sheet and dried overnight. The AFM probe was scanned quickly from left to right and slowly from top to bottom, and AFM images were acquired at a scanning rate of 0.56 Hz. The diameter distribution of CNFs in the AFM images was calculated using Image J software (Image J win-64).

[0064] The test results are as follows: AFM results are shown in Figure 2~Figure 4 As shown in Table 3, the CNFs of Examples 1-3 exhibited a clear filamentous structure, while the CNFs of Comparative Example 2 exhibited a bundle structure and were unevenly distributed. The diameter distribution of CNFs is shown in Table 3. The average diameter of the CNFs of Example 1 was the smallest at 23.33 nm, while the average diameter of the CNFs of Comparative Example 2 was the largest at 39.44 nm.

[0065] Table 3 Diameter distribution of CNFs

[0066] Note: Different letters (af) in the same column indicate significant differences among the values ​​( p <0.05).

[0067] Experimental Example 4: X-ray diffraction (XRD) analysis of cellulose nanofibers The crystallinity analysis of CNFs was performed by X-ray diffraction. Before the measurement, the sample powder was pressed into uniform flakes in the grooves of a glass holder. The test conditions were: 2θ range of 5° to 40°, rate of 5° / min, current of 40 mA, and voltage of 40 kV. The crystallinity index (CrI) was determined according to the Scherrer equation: Among them I 200 It is the maximum diffraction intensity of the cellulose crystal region, and the peak angle is 22.4°. am It is the minimum diffraction intensity of the amorphous region of cellulose, and the peak angle is 18.5°.

[0068] The test results are as follows: The crystallinity results are shown in Table 4. The crystallinity index of CNFs of Examples 1-3 is significantly higher than that of Examples 4 and Comparative Examples 1-2, wherein the crystallinity index of CNFs obtained in Example 1 is the highest at 39.41±0.43%, and the crystallinity index of CNFs obtained in Comparative Example 2 is the lowest at 36.16±0.20%. This indicates that the preferred conditions of the present invention significantly improve the crystallinity of CNFs.

[0069] Table 4 Crystallinity of CNFs

[0070] Note: Different letters (af) in the same column indicate significant differences among the values ​​( p <0.05).

[0071] Experimental Example 5: Analysis of Cellulose Nanofibers and Lignin Structure The structures of CNFs and lignin were analyzed by Fourier transform infrared spectroscopy (FTIR). The sample powder was thoroughly mixed with dry potassium bromide (KBr) powder at a ratio of 1:150. The mixture was then thoroughly mixed using an agate mortar. Subsequently, a hydraulic press was used to compress the mixture at a pressure of 10 MPa for 40 s. The uniform film was inserted into the FTIR device for spectral analysis. KBr was used as the background. The test conditions were as follows: the wave number was 400 cm -1 ~ 4000 cm -1 , scanned 64 times, with a resolution of 4 cm -1 .

[0072] The test results are as follows: FTIR results are as follows Figure 5 As shown, there are characteristic peaks of cellulose in the raw material sample (1423cm-1, 1372cm -1 、1315cm -1 、1161cm -1 , ), characteristic peaks of lignin (1511 cm -1 、833 cm -1 ) and hemicellulose characteristic peaks (1737 cm -1 、1251cm -1 ). Both the CNFs of Example 1 and the commercial CNFs have the characteristic peak of cellulose at 1423 cm -1 、1372 cm -1 、1315 cm -1 The peak detected at 1161 cm-1 can be attributed to the CH stretching vibration of cellulose. -1 The peak at 1511 cm-1 can be attributed to the CO stretching vibration of cellulose. -1 The absorption peak at 833 cm is caused by the CC stretching vibration of the phenylpropane aromatic ring in the lignin unit. -1 The absorption peak at is caused by CH of the aromatic ring in the lignin unit. This indicates that the GVL / H2O / NaCl co-solvent pretreatment in the present invention effectively extracts cellulose and lignin from the raw material.

[0073] Experimental Example 6: Analysis of Thermal Stability of Cellulose Nanofibers and Lignin The thermal stability of CNFs and lignin was determined by thermogravimetric analysis (TGA). The experimental conditions were as follows: under nitrogen conditions, at 10 °C min -1 The heating rate is from 30°C to 500°C.

[0074] The test results are as follows: The results are as follows Figure 6As shown, the maximum thermal degradation temperature of CNFs in Example 1 is 329.03±1.50°C, which is higher than that of commercial CNFs (maximum thermal degradation temperature is 297.45±1.25°C). The maximum thermal degradation temperature of lignin in Example 1 is 334.45±1.03°C, which is higher than that of commercial lignin (maximum thermal degradation temperature is 310.86±1.17°C). This shows that both CNFs and lignin prepared under the preferred conditions of the present invention have good thermal stability.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for processing agricultural by-products, characterized in that: include: S1: drying and crushing the agricultural by-product to obtain agricultural by-product powder; S2: mixing the agricultural byproduct powder with a co-solvent and reacting the mixture to obtain a mixed slurry; vacuum filtering the mixed slurry to obtain cellulose-rich solid and liquid fractions, respectively; The agricultural byproducts contain lignocellulose, and the co-solvent comprises a mixture of water and γ-valerolactone.

2. The method for processing agricultural by-products according to claim 1, characterized in that: In the co-solvent, the volume ratio of water to γ-valerolactone is (1~4): (1~4).

3. The method for processing agricultural byproducts according to claim 1 or 2, characterized in that S2 include: The agricultural byproduct powder, the co-solvent and the catalyst are mixed and reacted to obtain a mixed slurry after the reaction; the mixed slurry is vacuum filtered to obtain solid and liquid fractions rich in cellulose respectively; wherein the catalyst includes a metal salt; Preferably, the metal salt includes one or more of NaCl, MgCl2, AlCl3 and FeCl3; Further preferably, the concentration of the metal salt in the aqueous phase of the co-solvent is 5 wt % to 30 wt %.

4. The method for processing agricultural by-products according to claim 3, characterized in that: Based on the volume of the mixture of the co-solvent and the catalyst, 0.05-0.2 g of the agricultural by-product powder is added per milliliter of the mixture.

5. The method for processing agricultural by-products according to any one of claims 1 to 4, characterized in that: In S2, the reaction temperature is 70°C to 190°C; preferably, the reaction time is 1 h to 6 h.

6. The method for processing agricultural by-products according to any one of claims 1 to 5, characterized in that: S2 also includes the following processing steps: S3: The liquid fraction is mixed with water, and then allowed to stand and subjected to a first centrifugation treatment in sequence, and the obtained precipitate is lignin; at the same time, the cellulose-rich solid is bleached and subjected to a second centrifugation treatment in sequence, and then the obtained lower precipitate is mixed with water to obtain a suspension, and the suspension is subjected to high-pressure homogenization and freeze-drying in sequence to obtain cellulose nanofibers.

7. The method for processing agricultural by-products according to claim 6, characterized in that: The volume ratio of the liquid fraction to water is 1:(2-10); the rotation speed of the first centrifugal treatment is 7000 r / min-10000 r / min; preferably, the time of the first centrifugal treatment is 10 min-30 min; Preferably, the supernatant obtained from the first centrifugation treatment is subjected to vacuum distillation to recover water and γ-valerolactone respectively; And / or, the bleaching temperature is 70° C. to 90° C., the bleaching time is 4 h to 6 h; the concentration of the suspension is 0.1wt% to 0.5wt%, the pressure of the high-pressure homogenization is 20 MPa to 80 MPa, and the number of cycles of the high-pressure homogenization is 2 to 8 times.

8. Use of the method for processing agricultural by-products according to any one of claims 1 to 7 in the preparation of lignin and / or cellulose nanofibers; preferably, use of the method for processing agricultural by-products in the simultaneous preparation of lignin and cellulose nanofibers.

9. A lignin, characterized in that The method for treating agricultural by-products according to any one of claims 1 to 7 is used to prepare the agricultural by-products.

10. A cellulose nanofiber, characterized in that: The method for treating agricultural by-products according to any one of claims 1 to 7 is used to prepare the agricultural by-products.

Citation Information

Patent Citations

  • A method for preparing nanocellulose by acid hydrolysis of grass raw materials

    CN116536948B

  • A kind of phosphorylated cellulose nanofiber and preparation method thereof

    CN117230542B

  • Preparation method of lignin gel

    CN118702935A